2003
DOI: 10.1046/j.1523-1755.2003.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ERK pathway precedes tubular proliferation in the obstructed rat kidney

Abstract: This study has identified a discrete pattern of ERK activation in normal rat kidney and an increase in ERK activation following obstruction. The temporal and spatial relationship in which ERK activation preceded tubular cell proliferation suggest that ERK signaling plays a key role in tubular epithelial cell proliferation in the injured kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
86
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 21 publications
12
86
1
Order By: Relevance
“…UUO, a well characterized mouse model of renal fibrosis, was performed under general anesthesia as previously described. 36 Mice were killed on day1, day 3, or day 7 after UUO and renal tissues were harvested.…”
Section: Animalsmentioning
confidence: 99%
“…UUO, a well characterized mouse model of renal fibrosis, was performed under general anesthesia as previously described. 36 Mice were killed on day1, day 3, or day 7 after UUO and renal tissues were harvested.…”
Section: Animalsmentioning
confidence: 99%
“…Immunoperoxidase staining for phosphorylated JNK (p-JNK), c-Jun, p-c-Jun Ser63, p-c-Jun Ser73, p-ERK, and AQP2 was performed on 4-m sections of formalin-fixed tissue using antigen retrieval (microwave oven heating in 0.1 M sodium citrate [pH 6.0] for 10 min) followed by a three-layer avidin-biotin peroxidase complex (ABC) staining method (27). Immunoperoxidase staining for cleaved caspase-3 and ED1 ϩ macrophages was performed on formalin-fixed tissue sections without antigen retrieval and using a three-layer PAP staining method.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunoperoxidase staining for ␣-SMA used a three-layer PAP method on methylcarn-fixed tissue, and immunostaining for collagen IV used frozen sections with the avidin-biotin peroxidase complex method. Two-color immunostaining for AQP2 and p-JNK used formalin-fixed tissue sections as described previously (27).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Interestingly, immunohistochemical studies have recently revealed that the phosphorylated active form of ERK1/2 (pERK1/2) is expressed at detectable basal levels in the distal (but not in the proximal) nephron of normal rat kidney in vivo (14 -17). In the collecting duct Masaki et al (16) have recently shown that pERK1/2 is expressed in the principal cell and not in the intercalated cells. These in vivo data suggest that basal activity of ERK1/2 may have a specific physiological relevance in the principal cell of the collecting duct, independent of hormonal or ligand-induced stimuli and distinct from the hormonedependent effects observed in intercalated cells.…”
mentioning
confidence: 99%